A call to action to address escalating global threats to academic research - Gaelle Piret; Fun Man Fung; Josie Fullerton; Giuseppe Fico; Dmitriy Ponkratov; Wenxin Chen; Daniela Latorre; Kirsty Y. Wan; Nima Aghaeepour; Jules Welgryn; Adeel Razi; Patricia Silveyra; et al. (The Innovation)
This article is a call to action to address escalating threats to scientific progress that affect academic researchers across the globe. These threats include public mistrust of science, challenges in translating academic research to end-user applications, a disconnect between academics and policymakers, emerging barriers to international collaboration, and a reliance on conventional metrics to evaluate academic performance. This article presents various calls to action informed by exemplary approaches across the globe that serve as frameworks to drive beneficial transformation for researchers, academic institutions, and society.